Aromatic‐interaction‐mediated inhibition of β‐amyloid assembly structures and cytotoxicity. (23rd May 2017) - Xie, Hanyi; Peng, Jiaxi; Liu, Changliang; Fang, Xiaocui; Duan, Hongyang; Zou, Yimin; Yang, Yanlian; Wang, Chen
Abstract : Abnormal aggregation of β‐amyloid (Aβ) peptide plays an important role in the onset and progress of Alzheimer's disease (AD); hence, targeting Aβ aggregation is considered as an effective therapeutic strategy. Here, we studied the aromatic‐interaction‐mediated inhibitory effect of oligomeric polypeptides (K8Y8, K4Y8, K8W8) on Aβ42 fibrillization process. The polypeptides containing lysine as well as representative aromatic amino acids of tryptophan or tyrosine were found to greatly suppress the aggregation as evaluated by thioflavin T assay. Circular dichroism spectra showed that the β‐sheet formation of Aβ42 peptides decreased with the polypeptide additives. Molecular docking studies revealed that the oligomeric polypeptides could preferentially bind to Aβ42 through π–π stacking between aromatic amino acids and Phe19, together with hydrogen bonding. The cell viability assay confirmed that the toxicity of Aβ42 to SH‐SY5Y cells was markedly reduced in the presence of polypeptides. This study could be beneficial for developing peptide‐based inhibitory agents for amyloidoses. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : We demonstrate the inhibitory effect of oligomeric polypeptides containing representative aromatic amino acids of tryptophan and tyrosine (K8Y8, K4Y8, K8W8) on Aβ42 fibrillization process. Through direct binding at the N‐terminus of Aβ42 by π–π stacking between aromatic amino acids and Phe19, together with hydrogen bonds, the polypeptides can remarkably weaken the aggregation and fibrillization process of Aβ42, inhabit the β‐sheet formation of Aβ42, and reduce the cytotoxicity of S‐SY5Y cells.